2018
DOI: 10.1088/1674-1056/27/9/094210
|View full text |Cite
|
Sign up to set email alerts
|

Observation of 550 MHz passively harmonic mode-locked pulses at L-band in an Er-doped fiber laser using carbon nanotubes film

Abstract: We demonstrate a passively harmonic mode-locked (PHML) fiber laser operating at L-band using carbon nanotubes polyvinyl alcohol (CNTs-PVA) film. Under suitable pump power and appropriate setting of polarization controller (PC), the 54 th harmonic pulses at L-band are generated with the side mode suppression ratio (SMSR) better than 44dB, and repetition frequency of 503.37 MHz. Further increasing pump power leads to higher frequency of 550 MHz with compromised stability of 38.5 dB SMSR. To the best of our knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The highest achievable repetition rate in this scenario is 7.41 GHz, which corresponding to 378th harmonic order. The SMSR of 7.41 GHz pulses is 20.7 dB which is higher than the previous report of L-band PHML [9]- [11]. From the results, we know this maybe an alternative approach to obtain higher repetition rate when the process of increasing pump power is unavailable.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…The highest achievable repetition rate in this scenario is 7.41 GHz, which corresponding to 378th harmonic order. The SMSR of 7.41 GHz pulses is 20.7 dB which is higher than the previous report of L-band PHML [9]- [11]. From the results, we know this maybe an alternative approach to obtain higher repetition rate when the process of increasing pump power is unavailable.…”
Section: Resultsmentioning
confidence: 57%
“…But the corresponding SMSR at 5.88 GHz is only 19 dB [10]. Recently, 550 MHz L-band HML pulses have been obtained by means of a carbon nanotubes film [11]. It is found that L band HML relies on physical SA could hardly reach GHz repetition rate with >30 dB SMSR.…”
Section: Introductionmentioning
confidence: 99%
“…first proposed an EDFL that could emit passively harmonic modeā€locked pulses at the L band (1565ā€“1625 nm) with the application of CNTsā€PVA film. [ 115 ]…”
Section: Applications Of Nanomaterials In Ultrafast Lasersmentioning
confidence: 99%
“…By using this method, we obtained 42nd HML pulses at repetition frequency up to 1.15 GHz from film-type CNT SA-based fiber laser under pump power of 321 mW [201]. Taking advantage of wide operation wavelength range of CNTs, L-band PHML fiber laser using CNT film was proposed first in the same year [202]. We have carried out a systematic exploration on the effects of average cavity dispersion and spectral bandwidth on HML in L-band using similar laser scheme [203].…”
Section: G-hz Fiber Lasersmentioning
confidence: 99%